One‐Pot Synthesis of Pomegranate‐Structured Fe3O4/Carbon Nanospheres‐Doped Graphene Aerogel for High‐Rate Lithium Ion Batteries. Issue 13 (16th February 2016) - He, Dafang; Li, Lixian; Bai, Fengjuan; Zha, Chenyang; Shen, Liming; Kung, Harold H.; Bao, Ningzhong
Abstract: A unique hierarchically nanostructured composite of iron oxide/carbon (Fe3 O4 /C) nanospheres‐doped three‐dimensional (3D) graphene aerogel has been fabricated by a one‐pot hydrothermal strategy. In this novel nanostructured composite aerogel, uniform Fe3 O4 nanocrystals (5–10 nm) are individually embedded in carbon nanospheres (ca. 50 nm) forming a pomegranate‐like structure. The carbon matrix suppresses the aggregation of Fe3 O4 nanocrystals, avoids direct exposure of the encapsulated Fe3 O4 to the electrolyte, and buffers the volume expansion. Meanwhile, the interconnected 3D graphene aerogel further serves to reinforce the structure of the Fe3 O4 /C nanospheres and enhances the electrical conductivity of the overall electrode. Therefore, the carbon matrix and the interconnected graphene network entrap the Fe3 O4 nanocrystals such that their electrochemical function is retained even after fracture. This novel hierarchical aerogel structure delivers a long‐term stability of 634 mA h g −1 over 1000 cycles at a high current density of 6 A g −1 (7 C), and an excellent rate capability of 413 mA h g −1 at 10 A g −1 (11 C), thus exhibiting great potential as an anode composite structure for durable high‐rate lithium‐ion batteries. Abstract : Graphene aerogel electrode : A unique hierarchically nanostructured composite of Fe3 O4 /carbon nanospheres‐doped three‐dimensional (3D) graphene aerogel has been fabricated by a one‐pot hydrothermal strategy (see scheme). This material delivers superior cycling performance and excellent rate capability as an anode composite structure for durable high‐rate lithium‐ion batteries.